The Effects of Market Orientation and Innovation on Marketing Performance: A Survey of 5 SMEs in the Creative Industry Sector in Makassar City - Nurkaidah; Thamrin Abduh; Hasanuddin Remmang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
This study aims to determine how the influence of market orientation and innovation on marketing performance. The number of samples used was 50 employees who were divided from 5 Creative Industry MSME Sectors in Makassar city. Data collection was carried out using interviews, observation and questionnaires. The data analysis technique used is multiple linear regression analysis using the Statistical Program for Social Science (SPSS). The results of this study indicate that market orientation (X1) partially has a positive and significant influence on marketing performance. Product Innovation (X2) partially has a positive and significant impact on marketing performance. And simultaneously the two independent variables have a significant influence on marketing performance.